The Knowledge, Experiences and Perceptions of Nursing Students in Caring for a Patient with a Learning Disability: A Qualitative Study - Cromar-Hayes M; Lees C; Parkinson D; Deane K; Marshall H (Dove Medical Press, 2024)
Maxine Cromar-Hayes,1 Carolyn Lees,1 Denis Parkinson,1 Karen Deane,2 Helen Marshall1 1School of Allied Health Professions and Nursing, University of Liverpool, Liverpool, Merseyside, UK; 2Mersey Care NHS Foundation Trust, Liverpool, Merseyside, UKCorrespondence: Helen Marshall; Maxine Cromar-Hayes, School of Allied Health and Nursing, Institute of Population Health, University of Liverpool, Whelan Building, the Quadrangle, Brownlow Hill, Liverpool, L69 3GB, UK, Email Helen.marshall@liverpool.ac.uk; Maxine.Cromar-Hayes@liverpool.ac.ukPurpose: There is a known inequality in the healthcare provision for people with a learning disability, they have a poorer experience and a higher mortality rate than the general population. All registered health and social care organisations are required to provide training for staff in learning disability and autism, including how to communicate effectively and to provide reasonable adjustments. It has been suggested that this training needs to be available to those completing their nursing degrees.Methods: Focus groups were conducted with 21 adult nursing students. The qualitative data collected was analysed using a thematic framework to identify the main factors that contributed to how adult nursing students cared for those adults with a learning disability while on a clinical placement.Results: Generally, participants felt unprepared to care for adults with a learning disability. They described how they lacked knowledge and confidence, yet increased time on clinical placement was a facilitator to improving this. Role modelling of confident healthcare staff and personal experiences of having a relative with a learning disability all positively contributed to increasing confidence. Simulated practice and learning from those with lived experience were cited as a mechanism to enhance their knowledge. Communication with patients and between healthcare staff and families was seen as integral to being able to provide patient centred care.Conclusion: In a bid to ensure that those people with a learning disability have access to adequately skilled healthcare staff, adult nursing students need to be better prepared to provide care while on clinical placements. This will involve universities, clinical practice partners and those with a learning disability working together to collaboratively focus on training and education that develops confidence, knowledge and understanding which will then translate to excellent patient care.Keywords: intellectual disabilities, practice learning, nursing education